Pengaruh Kompetensi Dan Motivasi Berprestasi Terhadap Kinerja Guru Sekolah Dasar Dengan Kepuasan Kerja Sebagai Variabel Intervening - Hendri Ali Ardi (Akuntansi & Ekonomika, 2021)
This study aims to look at the effect of competence and achievement motivation on the performance of primary school teachers with job satisfaction as an intervening variable. The sample in this study amounted to 143 elementary school teachers, samples were taken using stratified random sampling. The researcher used path analysis as data analysis technique. This study found that (1) Teachers’ competence and achievement motivation influence simultaneously and partially on job satisfaction (2) Teacher’ competence, achievement motivation and job satisfaction simultaneously affect teachers’ performance, but the competence do not directly and significantly affect the performance of primary school teachers. But the competence affects teachers' performance indirectly through job satisfaction.